Late onset leptomeningeal and whole spine metastasis from supratentorial Glioblastoma multiforme: An uncommon manifestation of a common tumor - Divyam Sharma; Anshul Gupta; Gurupal S Dhillon; Satnam Singh Chhabra (Journal of Craniovertebral Junction and Spine, 2016)
Glioblastoma multiforme (GBM) is one of the most common and aggressive primary brain tumors, composing 12-20% of all the intracranial tumors in adults with a highly malignant course and average life expectancy of approximately 12-14 months following initial diagnosis. Leptomeningeal or intramedullary metastasis from primary GBM is a rare phenomenon with a poor prognosis. We present a rare case of GBM with late onset intramedullary, extramedullary, as well as leptomeningeal spinal metastasis.